Matrine: A Promising Natural Product With Various Pharmacological Activities - Zhang, Hong; Chen, Linlin; Sun, Xipeng; Yang, Quanjun; Wan, Lili; Guo, Cheng (Frontiers in Pharmacology, 2020)
Matrine is an alkaloid isolated from the traditional Chinese medicine Sophora flavescens Aiton. At present, a large number of studies have proved that matrine has an anti-cancer effect, can inhibit cancer cell proliferation, arrest cell cycle, induce apoptosis, and inhibit cancer cell metastasis. It also has the effect of reversing anti-cancer drug resistance and reducing the toxicity of anticancer drugs. In addition, studies have reported that matrine has a therapeutic effect on Alzheimer's syndrome, encephalomyelitis, asthma, myocardial ischemia, rheumatoid arthritis, osteoporosis and the like, and its mechanism is mainly related to the inhibition of inflammatory response and apoptosis. Its treatable disease spectrum spans multiple systems such as the nervous system, circulatory system, and immune system. The anti-disease effect and mechanism of matrine are diverse, so it has high research value. This review summarizes recent studies on the pharmacological mechanism of matrine, with a view to providing reference for subsequent research.